Supplier Selection In Malaysian Social Commerce Microenterprises - Haris, Juwairiah (2021)
Based on the Theory of Planned Behaviour (TPB), this study extended and included five supplier performance attributes which are service warranty, delivery, relationship, quality, and price. From this extended TPB, eight variables were investigated to examine the causal relationships among the variables with respect to selection intention and supplier selection behaviour.